2004
DOI: 10.1152/japplphysiol.00188.2004
|View full text |Cite
|
Sign up to set email alerts
|

Daily short-period gravitation can prevent functional and structural changes in arteries of simulated microgravity rats

Abstract: This study was designed to clarify whether simulated microgravity-induced differential adaptational changes in cerebral and hindlimb arteries could be prevented by daily short-period restoration of the normal distribution of transmural pressure across arterial vasculature by either dorsoventral or footward gravitational loading. Tail suspension (Sus) for 28 days was used to simulate cardiovascular deconditioning due to microgravity. Daily standing (STD) for 1, 2, or 4 h, or +45 degrees head-up tilt (HUT) for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
4
25
1
Order By: Relevance
“…Application of the rat hindlimb unloading model over an 11-day period to identify mechanisms of lipid dysregulation during reduced standing/nonexercise ambulation have also had this concern (1) and thus have employed an intermittent phase each day where the rat is returned to the standing position. At least in rats, intermittent reloading was able to successfully prevent skeletal muscle atrophy (1) and adverse changes in both myocardial contractility (66) and the cerebral vasculature (67). Lipoprotein lipase function.…”
Section: Contrasting Exercise Physiology and Inactivity Physiologymentioning
confidence: 99%
“…Application of the rat hindlimb unloading model over an 11-day period to identify mechanisms of lipid dysregulation during reduced standing/nonexercise ambulation have also had this concern (1) and thus have employed an intermittent phase each day where the rat is returned to the standing position. At least in rats, intermittent reloading was able to successfully prevent skeletal muscle atrophy (1) and adverse changes in both myocardial contractility (66) and the cerebral vasculature (67). Lipoprotein lipase function.…”
Section: Contrasting Exercise Physiology and Inactivity Physiologymentioning
confidence: 99%
“…The technique of tail suspension with modification from our laboratory has been described in detail previously [22], [28]. Briefly, the rats were maintained in an about −30° head-down tilt position with their hindlimbs unloaded to simulate the cardiovascular effect of microgravity.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the adaptation changes yet exhibits regional differences along different arterial segments in cerebral circulation. As we have shown, in the case of basilar artery, a large cerebral artery that also contributes importantly to cerebrovascular resistance [23], S+D can prevent both the enhanced vasoreactivity and hypertrophic remodeling that might occur due to SUS alone [22]; however, in MCA, a proximal resistance artery, it can prevent only hypertrophy but not the enhanced myogenic tone and increased vasoreactivity [21], [24]. To evaluate further the countermeasure effectiveness of IAG on cerebral small resistance arteries, it is also essential to understand their active and passive mechanical properties.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This daily free exercise might have influenced the vascular innervation density by augmenting the countermeasure effect of movement in the tilt cage. Sun et al [26] found that the depression in the vasoconstrictor responsiveness of rat femoral arterial rings induced by 4 weeks of tail suspension was prevented either by daily HUT for 4 h or by being horizontal for 1 h. In our previous head-up tilt experiments, the same 1 h grooming period was provided for the animals, and significant differences have been observed in the same parameters between control and tilted animals [2]. Contrary to tail suspension, however, the animals in our experiments were freely moving in the tilt cages throughout the whole tilting period [20,21], and we do not believe that the additional movement during the daily grooming period could substantially influence the observed innervation densities.…”
Section: Discussionmentioning
confidence: 99%